Strategi Produksi Pangan Organik Bernilai Tambah Tinggi yang Berbasis Petani - Musa Hubeis; Mukhamad Najib; Hardiana Widyastuti; Nur Hadi Wijaya (Jurnal Ilmu Pertanian Indonesia, 2013)
Food security is a system consists of availability, distribution, and consumption subsystems. Food availability subsystem functions in guaranting food supply, in terms of quantity, quality (certification), variability, and safety. The main problem in materializing security of organic food commodities are quantity and quality of organic food, particularly vegetables. In other words, the organic vegetable can affect farmer’s economic situation in different way depending on the adopted particular technolog. Therefore, the objectives of this study are (1) to describe the characteristics of organic vegetable products, (2) to identify internal and external factors related to the production of organic vegetables with a farmer-based high added value, and (3) to formulate a strategy of the production of organic vegetables with a farmer-based high added value (certified). Data were collected by purposive sampling and analyzed using matrix analysis tools of internal factor evaluation, external factor evaluation, internal external, and focus group discussion, as the basis for analyzing strengths, weaknesses, opportunities, and threats (SWOT), followed by quantitative strategic planning matrix (QSPM) to obtain the main alternative strategy for the development of organic vegetable with premium price. The study was carried out in Garut, West Java. This study confirmed 3 main strategic issues for the development of organic vegetables in the region, that is, market, organic vegetable production, and human resource.